2021
DOI: 10.1002/anie.202015129
|View full text |Cite
|
Sign up to set email alerts
|

Scan and Unlock: A Programmable DNA Molecular Automaton for Cell‐Selective Activation of Ligand‐Based Signaling

Abstract: Selective modulation of ligand–receptor interaction is essential in targeted therapy. In this study, we design an intelligent “scan and unlock” DNA automaton (SUDA) system to equip a native protein‐ligand with cell‐identity recognition and receptor‐mediated signaling in a cell‐type‐specific manner. Using embedded DNA‐based chemical reaction networks (CRNs) on the cell surface, SUDA scans and evaluates molecular profiles of cell‐surface proteins via Boolean logic circuits. Therefore, it achieves cell‐specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…These can be categorized into two groups:( 1) DNA-based agonists for GFRs, [16][17][18][19][20] and (2) artificial switching of GFR activity depending on external stimuli using DNAa ptamer-based chemical tools. [38][39][40][41][42][43][44] Thep resent research provides studies within the former group.U sing several cell-based assays,w e showed that designing tandem dimer ligands by tethering monomeric ligands with different affinities is an effective approach for developing receptor agonists with desired properties.N otably,t he herein described aptamer dimer design achieved fine tuning of the E max value without significant potency loss,w hich has not been achieved using the previously available strategies.I nt he original report on the development of agonistic Met aptamers, [17] some Met agonists with reduced E max values were identified during the optimization of the aptamer configurations;h owever,t heir structure-activity relationship remains unclear. Importantly, the effects of these agonists on different cellular phenotypes and the utility of such partial agonists were not demonstrated in that previous study.Hence,the design concept proposed in the present study will provide important insights into the development of partial agonists for growth factors and cytokines.I na ddition, the herein developed partial Met agonists could be used to regulate therapeutically relevant cellular activities by eliciting moderate receptor signaling.I t should be noted that we cannot exclude the possibility that the stem deletion affected the agonism of the aptamers by changing the geometry of the aptamer-receptor complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be categorized into two groups:( 1) DNA-based agonists for GFRs, [16][17][18][19][20] and (2) artificial switching of GFR activity depending on external stimuli using DNAa ptamer-based chemical tools. [38][39][40][41][42][43][44] Thep resent research provides studies within the former group.U sing several cell-based assays,w e showed that designing tandem dimer ligands by tethering monomeric ligands with different affinities is an effective approach for developing receptor agonists with desired properties.N otably,t he herein described aptamer dimer design achieved fine tuning of the E max value without significant potency loss,w hich has not been achieved using the previously available strategies.I nt he original report on the development of agonistic Met aptamers, [17] some Met agonists with reduced E max values were identified during the optimization of the aptamer configurations;h owever,t heir structure-activity relationship remains unclear. Importantly, the effects of these agonists on different cellular phenotypes and the utility of such partial agonists were not demonstrated in that previous study.Hence,the design concept proposed in the present study will provide important insights into the development of partial agonists for growth factors and cytokines.I na ddition, the herein developed partial Met agonists could be used to regulate therapeutically relevant cellular activities by eliciting moderate receptor signaling.I t should be noted that we cannot exclude the possibility that the stem deletion affected the agonism of the aptamers by changing the geometry of the aptamer-receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…These can be categorized into two groups:( 1) DNA-based agonists for GFRs, [16][17][18][19][20] and (2) artificial switching of GFR activity depending on external stimuli using DNAa ptamer-based chemical tools. [38][39][40][41][42][43][44] Thep resent research provides studies within the former group.U sing several cell-based assays,w e showed that designing tandem dimer ligands by tethering monomeric ligands with different affinities is an effective approach for developing receptor agonists with desired properties.N otably,t he herein described aptamer dimer design achieved fine tuning of the E max value without significant potency loss,w hich has not been achieved using the previously available strategies.I nt he original report on the development of agonistic Met aptamers, [17] some Met agonists with reduced E max values were identified during the…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have demonstrated the potential of DNA aptamers to regulate the activity of growth factor receptors (GFRs). These can be categorized into two groups: (1) DNA‐based agonists for GFRs, [16–20] and (2) artificial switching of GFR activity depending on external stimuli using DNA aptamer‐based chemical tools [38–44] . The present research provides studies within the former group.…”
Section: Discussionmentioning
confidence: 99%
“…These can be categorized into two groups:( 1) DNA-based agonists for GFRs, [16][17][18][19][20] and (2) artificial switching of GFR activity depending on external stimuli using DNAa ptamer-based chemical tools. [38][39][40][41][42][43][44] Thep resent research provides studies within the former group.U sing several cell-based assays,w e showed that designing tandem dimer ligands by tethering monomeric ligands with different affinities is an effective approach for developing receptor agonists with desired properties.N otably,t he herein described aptamer dimer design achieved fine tuning of the E max value without significant potency loss,w hich has not been achieved using the previously available strategies.I nt he original report on the development of agonistic Met aptamers, [17] some Met agonists with reduced E max values were identified during the…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that many of these logic gates can be applied for multiparameter biosensing, regulating, and even manipulating biological systems due to the good biocompatibility and responsive ability to multiple biological signals. 101,102 In 2012, Willner and coworkers reported pHprogrammable DNA logic arrays for mimicking sophisticated biomachineries. The DNA nanoarrays were constructed by Mg 2+ -and UO 2þ 2 -dependent DNAzymes/ substrates libraries.…”
Section: Multiple Stimuli Triggered Logic Gatesmentioning
confidence: 99%